Quality assessment and safety of fresh-cut melon coated in chitosan matrix added with microencapsulated bioactive extracted from byproducts of acerola - Samira Pereira Moreira (2014)
The minimal processing of fruits and vegetables offers the consumer food fresh and practicality. However, these products rapidly lose quality after processing due to physical changes and their consequential biochemical reactions that can reduce the nutritional value and favours besides the growth of deteriorant and pathogenic microorganisms. Thus, this study aimed to develop a system of active packaging, consisting of an microencapsulated antimicrobial edible coating using chitosan added with bioactive compounds extracted from byproducts of processing of acerola (Malpighia emarginata D.C.) for minimally processed melon to maintain the quality and microbiological safety of this product. The parameters extraction of bioactive compounds of lyophilized byproducts (seed, peel and fibers) were optimized as the rotation speed, extraction time, extraction solution and by proportion: extraction solution. The extract showed high content of antioxidants, especially polyphenols. The coating was produced from the 1:1 mixture (v / v) solution of chitosan and 1% ethanolic extract of bioactive compounds, and chitosan itself as the encapsulating material. Two treatments (coated and uncoated melons) each 3 days during 12 days of storage at 10˚C Â 1 were evaluated as attributes of quality, bioactive compounds, total antioxidant activity, spoilage and pathogenic microorganisms (Salmonella spp and Listeria monocytogenes). The results showed that the coating samples provided the melons minor loss of firmness and weight, increased the content of yellow flavonoids and total extractable polyphenols, consequently high total antioxidant activity when compared to control cubes. Moreover, the coating showed antimicrobial activity against bacteria (mesophilic, psicotrophic and lactic), molds and yeasts in coated fruits. The novel product is according to RDC ANVISA 12˚ whose recommendation for fresh fruits must be absence of Salmonella spp in 25 g. Therefore, this coating is a viable alternative for maintain the quality of minimally processed melons , since it provided better nutrition by maintaining bioactive fruit compounds, the safety, beyond the scope of the life of the product.